Assessment of the Correlation Between Weight Status and the Frequency of Dietician Interviews in Sleeve Gastrectomy Patients - BATAR, NAZLI; SEVDİN, SEZEN; Güçlü, Duygu; KERMEN, SEDA (Springer, 2021)
Purpose The aim of this study was to evaluate the relationship between the weight status of sleeve gastrectomy patients during the first two postoperative years and the frequency of dietician interviews. Materials and Methods This was a retrospective cross-sectional study, and the subjects were patients who had surgery at a special obesity clinic, Bariatriklab, in Istanbul, Turkey, between February 01, 2014, and February 01, 2018.The mean age +/- standard deviation of the participants was 38.8 +/- 11.9 years. The mean body mass index (BMI) +/- standard deviation was 44.2 +/- 6.1 kg/m(2)preoperatively. The preoperative (pre-op) and 12-, 18-, and 24-month postoperative (post-op) weights and the frequency of interviews with dieticians for 2 years after the operation were collected, and statistical analysis was performed using SPSS ver. 23.0. Results A total of 247 laparoscopic sleeve gastrectomy (LSG) patients, 161 women (65.2%) and 86 men (34.8%), were evaluated in this study. As the frequency of dietician interviews increased in the first year, the amount of excess weight loss (EWL) increased in the second year (p < 0.01). In addition, as the frequency of dietician interviews increased in the second year, the amount of EWL in the second year decreased (p < 0.01). The frequency of dietician counseling among participants who did not experience weight loss between 12 and 24 months was significantly higher than that among those who experienced weight loss (p < 0.05). Conclusion It should not be forgotten that bariatric surgery requires teamwork, and patients should be cared for with an interdisciplinary approach. Dieticians play an important role in changing nutritional habits and making them sustainable.
Keywords: Bariatric Surgery; Weight Regain; Dietician Interviews